A case report of Nocardia cyriacigeorgica presenting as cellulitis with multiple discharging sinuses - Archana Bora; Laxmi Rathore; Prabhat K Khatri; C S Chattopadhyay (Wolters Kluwer Medknow Publications, 2019)
Nocardia spp. are filamentous Gram positive bacteria that are ubiquitous soil saprophytes. The majority of nocardial infections occur in severely immunocompromised patients who are particularly susceptible to pulmonary disease and dissemination. Extrapulmonary nocardiosis is relatively common and can occur through hematogenous dissemination or a contiguous spread of necrotizing pneumonitis. Primary cutaneous and soft tissue nocardiosis can result from traumatic injury to the skin that involves contamination with soil. After skin inoculation, a superficial abscess or localized cellulitis can develop. Co-trimoxazole is the drug of choice for all types of nocardiosis. We are reporting a case of Nocardia cyriacigeorgica presenting as cellulitis followed tooth extraction.